An Evidence-Based Education Program for Adults about Child Sexual Abuse (“Prevent It!”) That Significantly Improves Attitudes, Knowledge, and Behavior - Martin, Erin K.; Silverstone, Peter H. (Frontiers in Psychology, 2016)
Here we describe the development of an evidence-based education program for adults about childhood sexual abuse (CSA), called Prevent It! Uniquely, the primary goal of this program was to change the behaviour of participants, as well as to increase knowledge about CSA and positive attitudes towards it. A comprehensive review shows no previous similar approach. The program includes a detailed manual to allow standardized administration by trained facilitators, as well as multiple video segments from CSA survivors and professionals. A total of 23 program workshops were run, with 366 adults participating. Of these, 312 (85%) agreed to take part in the study. All completed baseline ratings prior to the program and 195 (63% of study sample) completed follow-up assessments at 3-months. There were no significant differences between the demographic make-up of the baseline group and the follow-up group. Assessments included demographic data, knowledge, attitudes, and several measures of behaviour (our primary outcome variable). Behavioural questions asked individuals to select behaviours used in the previous 3-months from a list of options. Questions also included asking “how many times in the previous 3-months” have you “talked about healthy sexual development or child sexual abuse with a child you know”; “suspected a child was sexually abused”; “taken steps to protect a child”; or “reported suspected sexual abuse to police or child welfare”? The majority of attendees were women, with the commonest age group being between 30 – 39 years old. Approximately 33% had experienced CSA themselves. At 3-month follow-up there were highly statistically significant improvements in several aspects of behaviour and knowledge, and attitudes regarding CSA. For example, the number of subjects actively looking for evidence of CSA increased from 46% at baseline to 81% at follow-up, while the number of subjects who actively took steps to protect children increased from 25% at baseline to 48% at follow-up. For general public adults, this is the first program designed using the current evidence base for effective training in CSA examining longer-term outcomes and the first to focus on actual behavioural outcomes. The results suggest it is highly effective and support its widespread use.